'Equality of Intelligences': Exploring the Barriers to Engagement in Modern and Contemporary Art through a Peer‐to‐Peer Workshop at Tate Modern. (October 2014) - Sayers, Esther
Abstract The data presented in this article explores the effect on pedagogy when inclusion initiatives are bound up with learning objectives. It explores the generation of critical thinking skills in learning programmes at Tate Modern. Effective art education empowers young people to take a critical stance and in gallery education a decision has to be made: are programmes for young people about encouraging them to think about art or inviting them to think? I explore the position and status given to artworks and to young people's interpretations of those works through data gathered during a peer‐led workshop. I illustrate the ways in which new critical voices are able to emerge and contrast them with potential pedagogic pitfalls in which such approaches become exclusive and ultimately work against their emancipatory aims. People who work in galleries and museums are 'cultivated individuals'. They can easily take for granted their judgements about art and consider them to be 'natural'. Because of this a disconnection can occur between people who are not acculturated and those who are. The purpose of this study is to shed light on cultural exclusion by exploring dialogue about art produced during a peer‐led workshop.